Ein Meister an der Peripherie des Kapitalismus Machado de Assis - Schwarz, Roberto (De Gruyter, 2023)
This study examines The Posthumous Memoirs of Brás Cubas (1880), the magnum opus of Brazilian author Machado de Assis. Those interested in literature and cultural theory will find here a shining model of that which affects the relationship between social process and cultural form. Schwarz goes beyond the paradigms of critical theory to shed new light on questions of postcolonial thought.